Screening and Isolation of Bacterial Strains Able to Degrade Trimethylamine - Sebastião V. T. F. de Almeida; Kilian Neves; Carla C. C. R. de Carvalho (Microorganisms)
Methylamines are present in numerous organisms and microorganisms capable of de novo trimethylamine (TMA) production are widely distributed, including microalgae. However, such compounds may hamper the application of microalgae biomass in commercially interesting products, such as food and feed products, due to the strong fishy smell. In the present study, several bacteria able to degrade TMA were isolated. Among them, a Staphylococcus saprophyticus strain was found particularly suitable to degrade TMA. After finding the best culture conditions, a bioprocess system was developed allowing the degradation of TMA from microalgae in a reactor by S. saprophyticus cells present in a second reactor without direct contact with media from both reactors. The system was found to be limited by TMA transfer through the gas phase, with the cells being able to degrade all available TMA.